2015
DOI: 10.1016/j.apcatb.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

A study of the hydrodenitrogenation of propylamine over supported nickel phosphide catalysts using amorphous and nanostructured silica supports

Abstract: Pyrolysis of animal by-products provides pyro-oil that contains about 10 wt% nitrogen mainly in aliphatic compounds and virtually no sulfur. The nitrogen should be removed from the oil preferably by hydrodenitrogenation (HDN) to obtain liquid fuel and ammonia. In order to understand the catalytic HDN processes of such bio-oils the HDN of propylamine (PA) was studied as model reaction over silica-supported Ni 2 P and Ni catalysts. Catalysts were prepared by H 2 -reduction of catalyst precursor NiO/phosphated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
0
16
1
Order By: Relevance
“…Interestingly, no obvious sign for the formation of protonated PA (PAH + ) is discernible in the spectra, although PA also appears among the gas phase reaction products. Our earlier study on the hydroconversion of PA showed that the δ s (NH 3 + ) band of PAH + should appear at 1530 cm -1 [13]. Note however, that in the present study PA is formed by the hydrogenation of PN and it is intermediate of DPA formation.…”
Section: Catalytic Hydroconversion Of Pncontrasting
confidence: 44%
See 1 more Smart Citation
“…Interestingly, no obvious sign for the formation of protonated PA (PAH + ) is discernible in the spectra, although PA also appears among the gas phase reaction products. Our earlier study on the hydroconversion of PA showed that the δ s (NH 3 + ) band of PAH + should appear at 1530 cm -1 [13]. Note however, that in the present study PA is formed by the hydrogenation of PN and it is intermediate of DPA formation.…”
Section: Catalytic Hydroconversion Of Pncontrasting
confidence: 44%
“…With the aim to generate knowledge about the HDN processes of feeds containing aliphatic N-compounds in high concentration and virtually no sulfur we studied the catalytic HDN reaction of simple compounds, representing the Norganic molecules of MBM pyro-oil, over supported Ni 2 P catalysts. In previous studies we reported about the HDN of PA [12,13] mA) and a proportional counter. Crystallite sizes were determined from the line broadening using the Scherrer equation.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal phosphides, although discovered in the 18th century, in contrast with metallic, metal oxide, and metal chalcogenide (quantum dot) nanoparticles, have attracted significant scientific interest in the past few decades due to their potential applications, mainly in the fields of catalysis, replacing noble and precious metals, semiconductors, and magnetic materials. 1−5 With respect to catalysis, transition metal phosphides are being evaluated as hydrotreating catalysts for hydro-desulfurization (HDS), 6−9 hydro-denitrogenation (HDN), 10 hydroprocessing (HPC), 11 hydrogen evolution reaction (HER) 12−20 processes, and electrochemical energy storage. 21,22 Among transition metal phosphides, nickel phosphides have been attracting greater interest because they exhibit superior catalytic activities, especially in the HDS reactions, in comparison with other metal phosphides such as Fe 2 P, MoP, WP, and Pd 2 P 5 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…With respect to catalysis, transition metal phosphides are being evaluated as hydrotreating catalysts for hydro-desulfurization (HDS), hydro-denitrogenation (HDN), hydroprocessing (HPC), hydrogen evolution reaction (HER) processes, and electrochemical energy storage. , Among transition metal phosphides, nickel phosphides have been attracting greater interest because they exhibit superior catalytic activities, especially in the HDS reactions, in comparison with other metal phosphides such as Fe 2 P, MoP, WP, and Pd 2 P 5 . Among nickel phosphides, the hexagonal one, Ni 2 P, is the most active HDS catalyst in comparison with other nickel phosphides such as Ni 12 P 5 , Ni 5 P 4 , and NiP 2 . , Therefore, the development of methodologies for the selective synthesis of crystal structure-controlled nickel phosphide catalysts has become essential. Up to date, various synthetic routes have been used for the synthesis of Ni 2 P nanoparticles in various morphologies, such as solid and hollow nanoparticles, , branched nanoparticles, nanorods, and nanowires .…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal phosphides, although they discovered in the 18 th century, in contrast with metallic, metal oxides and metal chalcogenide (quantum dots) nanoparticles, attract significant scientific interest in the last decades because of their potential applications, mainly in the fields of catalysis, replacing noble and precious metals, semiconductors and magnetic materials. [1][2][3][4][5] With respect to catalysis, transition metal phosphides are being evaluated as hydro-treating catalysts for hydrodesulfurization (HDS) [6][7][8][9] hydrodenitrogenation (HDN) 10 , hydroprocessing (HPC) 11 , and hydrogen evolution reaction (HER) [12][13][14][15][16][17][18][19][20] processes and electrochemical energy storage. 21,22 Among transition metal phosphides, nickel phosphides are attracting the greater interest because exhibits superior catalytic activities, especially in the HDS reactions, in comparison with other metal phosphides like Fe2P, MoP, WP, and Pd2P5.…”
Section: Introductionmentioning
confidence: 99%